Dental student’s satisfaction towards orthodontic laboratory work from RSGM Dental Laboratory - Sianiwati Goenharto; Dini Setyowati; Elly Rusdiana (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Customer satisfaction plays an important role in the success and continuity of a business. Dental Laboratory of RSGM Faculty of Dental Medicine Universitas Airlangga provides services for Faculty of Dental Medicine, Universitas Airlangga students enrolled in a dental profession program. One of services offered is making of removable orthodontic appliances. Until now there has been no research on customer satisfaction after the appliances made in the laboratory. Purpose: This study was conducted to determine whether Universitas Airlangga dental students as customers were satisfied with the work of the RSGM Dental laboratory, particularly in orthodontics. Method: An analytic observational study was carried out on 48 Faculty of Dental Medicine Universitas Airlangga students who were enrolled in a dental profession program and made removable orthodontic appliances in RSGM Dental Laboratory. The students were asked to fill out a questionnaire about satisfaction regarding the timeliness, the suitability of results, the services provided, the quality of both active and passive components, the ease of insertion and activation. Data were analyzed descriptively. The relationship between satisfaction towards the quality of clasp, spring, bow and satisfaction towards the quality of acrylic plate to the ease of insertion were analyzed with Fischer exact test. The relationship between satisfaction towards the quality of clasp, spring, bow and satisfaction towards the quality of acrylic plate to the ease of activation were analyzed by chi square. Result: Respondents who were satisfied with the timeliness of work were 54.17%, the suitability of the results of the query were 79.17%, the services provided were 95.83%, the results of clasp, bow and spring were 72.92%, the results of acrylic plate were 77.08%, the ease of insertion were 54.17%, and the ease of activation were 89.58%. The results of the statistical analysis showed a significant correlation between the ease of insertion and the quality of clasp, spring and bow (p = 0.01) as well as acrylic plate made (p = 0.045 <0.05), however, there was no significant correlation between the ease of activation with quality of clasp, spring and bow (p = 0.08) and the acrylic plate made (p = 0.337 (p> 0.05)). Conclusion: It was concluded that the majority of respondents are satisfied with the results of removable orthodontic appliances produced, but punctuality still needs to be improved.